The Professional Experience of Mathematics Teachers in Promoting Students’ Transversal Skills in Basic and Secondary Schools - Kaļķe, Baiba; Āboltiņa, Līga; Lāma, Gatis (Journal of Education Culture and Society, 2026)
Aim. The aim of the study is to explore the professional experience of basic and secondary school mathematics teachers in developing transversal skills. Methods. In total, 126 mathematics teachers and 512 students participated in the study. Students’ transversal skills assessed by teachers were compared with the opportunities provided to develop these skills in both basic and secondary schools. Descriptive statistics and Spearman’s rank correlations were used. Secondary school students’ transversal skill self-assessments were also compared with teacher assessments. The Mann–Whitney U test was conducted. Results. The assessment of basic school students’ transversal skills in many areas does not correlate with the assessment of the opportunities provided. At secondary school, a correlation exists between the assessment of most transversal skills and the evaluation of the opportunities for their development. Additionally, secondary school students rate their skills higher than teachers do in almost all transversal skills; however, this difference is not always statistically significant. Conclusions. The results indicate that although Latvian education policy documents emphasise the development of transversal skills at all levels, in practice this integration often occurs in a fragmented manner, as teachers lack a shared understanding and methodological support for effectively fostering these skills. Teachers believe they provide students with opportunities to develop transversal skills; however, these opportunities do not always translate into actual skill development. Furthermore, the differences between students’ self-assessments and teachers’ evaluations highlight the need for a more unified understanding of how to foster transversal skills effectively.